2020
DOI: 10.3390/medicina56110585
|View full text |Cite
|
Sign up to set email alerts
|

On the Playing Field to Improve: A Goal for Autism

Abstract: In recent years, there has been a renewed attention to lifestyle-based interventions in people with autism spectrum disorder. The positive effects of physical exercise programs have been well documented both in healthy people and in people with disabilities in the fields of psychological well-being, cognitive outcome and medical health. There is much less evidence about the opportunity to attempt a team-group sport for people with autism. Although researchers seem to suggest an overall positive effect, playing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 62 publications
0
1
1
2
Order By: Relevance
“…In the current study, no sex differences were found for participation in sports, which may be due to overall low participation rates as a result of ASD-related challenges, such as motor and social difficulties, peer exclusion, or a limited number of accommodating sports programs ( Menear & Neumeier, 2015 ; Vetri & Roccella, 2020 ). In prior research, typically developing adolescent males and females have similar rates of overall participation, with males more often engaging in sports and females more often engaging in clubs ( Im et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 65%
“…In the current study, no sex differences were found for participation in sports, which may be due to overall low participation rates as a result of ASD-related challenges, such as motor and social difficulties, peer exclusion, or a limited number of accommodating sports programs ( Menear & Neumeier, 2015 ; Vetri & Roccella, 2020 ). In prior research, typically developing adolescent males and females have similar rates of overall participation, with males more often engaging in sports and females more often engaging in clubs ( Im et al, 2016 ).…”
Section: Discussioncontrasting
confidence: 65%
“…Our systematic review critically appraises the literature to date on the effects of PA/exercise interventions in young adults with ASD between 19 and 30 years. Most previous reviews have assessed the effects of PA/exercise interventions in children with ASD (Bodnar et al, 2020; Chan et al, 2021; Djordjević et al, 2022; Doreswamy et al, 2020; Flori & Angeli, 2021; Healy et al, 2019; Huang et al, 2020; Liang et al, 2022; Ruggeri et al, 2020; Teh et al, 2021; Vetri & Roccella, 2020). These reviews suggested positive effects of PA interventions on motor performance, autism severity, as well as social communication, behavioral, and cognitive skills.…”
Section: Introductionmentioning
confidence: 99%
“…(2018) a prática de atividades físicas quando elaboradas de forma específica, auxiliam no desenvolvimento motor, melhoram as habilidades de socialização e de foco. Continuando a relação exercício físico e contexto social autores como Vetri, et al, (2020) relatam em seu estudo uma ligação positiva entre atividades físicas e bem-estar, especialmente em um contexto social, pode representar uma excelente e adicional saída saudável contra transtornos psiquiátricos, através de esportes coletivos, conseguem os benefícios no comportamento, desenvolvimento de habilidades físicas e motoras e atingir o ápice da socialização. Já Águiar, Renata Pereira et al (2017) também relata em seus estudos que a prática de exercícios como a caminhada, equinoterapia e atividades aquáticas para pessoas com TEA melhoram significativamente melhora nas capacidades de comunicação, redução do comportamento antissocial e de comportamentos estereotipados e agressivos.…”
Section: Discussionunclassified